Crime and punishment in Islamic law: Theory and practice from the sixteenth to the twenty-first century - Peters, Rudolph (Cambridge University, 2013)
Rudolph Peters' book is about crimes and their punishments as laid down in Islamic law. In recent years some Islamist regimes, such as those of Iran, Pakistan, Sudan and the northern states of Nigeria have reintroduced Islamic law in place of Western criminal codes. This was after the abolition of Islamic criminal law in the nineteenth and twentieth centuries. Previously, during the pre-modern period, Islamic criminal law was applied across the Muslim world and there are many examples of that application in the abundant archives and other sources of the period. Peters gives a detailed account of the classical doctrine and traces the enforcement of criminal law from the Ottoman period to the present day. The accounts of actual cases which range from theft to banditry, murder, fornication and apostasy shed light on the complexities of the law, and the sensitivity and perspicacity of the qadis who implemented it. This is the first single-authored account of both the theory and practice of Islamic criminal law. It will be invaluable for students, and scholars in the field, as well as for professionals looking for a comprehensive coverage of the topic.